Identification of two compound heterozygous VPS13A large deletions in chorea-acanthocytosis only by protein and quantitative DNA analysis - Spieler, Derek; Velayos-Baeza, Antonio; Mühlbäck, Alžbeta; Castrop, Florian; Maegerlein, Christian; Slotta-Huspenina, Julia; Bader, Benedikt; Haslinger, Bernhard; Danek, Adrian (Molecular genetics & genomic medicine, 2020)
BACKGROUND: Chorea-acanthocytosis (ChAc; OMIM #200150) is a rare autosomal recessive condition with onset in early adulthood that is caused by mutations in the vacuolar protein sorting 13A (VPS13A) gene encoding chorein. Several diagnostic genomic DNA (gDNA) sequencing approaches are widely used. However, their limitations appear not to be acknowledged thoroughly enough. METHODS: Clinically, we deployed magnetic resonance imaging, blood smear analysis, and clinical chemistry for the index patient's characterization. The molecular analysis of the index patient next to his parents covered genomic DNA (gDNA) sequencing approaches, RNA/cDNA sequencing, and chorein specific Western blot. RESULTS: We report a 33-year-old male patient without functional protein due to compound heterozygosity for two VPS13A large deletions of 1168 and 1823 base pairs (bp) affecting, respectively, exons 8 and 9, and exon 13. To our knowledge, this represents the first ChAc case with two compound heterozygous large deletions identified so far. Of note, standard genomic DNA (gDNA) Sanger sequencing approaches alone yielded false negative findings. CONCLUSION: Our case demonstrates the need to carry out detection of chorein in patients suspected of having ChAc as a helpful and potentially decisive tool to establish diagnosis. Furthermore, the course of the molecular analysis in this case discloses diagnostic pitfalls in detecting some variations, such as deletions, using only standard genomic DNA (gDNA) Sanger sequencing approaches and exemplifies alternative methods, such as RNA/cDNA sequencing or qRT-PCR analysis, necessary to avoid false negative results.
Keywords: chorein; kvantitativní polymerázová řetězová reakce; Vesicular Transport Proteins; genetické testování; compound heterozygosity; Blotting, Western; Humans; lidé; western blotting; heterozygot; Genetic Testing; Heterozygote; Male; vezikulární transportní proteiny; Adult; deletion; Real-Time Polymerase Chain Reaction; mužské pohlaví; Neuroacanthocytosis; VPS13A; chorea-acanthocytosis; choreoakantocytóza; dospělí; delece genu; Gene Deletion